2017
DOI: 10.1111/his.13295
|View full text |Cite
|
Sign up to set email alerts
|

What's new in pituitary pathology?

Abstract: The increasing recognition of pituitary disorders and their impact on quality of life and longevity has made understanding of this small gland a subject of paramount importance. Pituitary pathology has seen many significant studies that indicate progress in identification and classification of pituitary lesions, as well as improved management strategies for patients. In this review, we outline six major areas of advances: (i) changes in terminology from 'adenoma' to 'pituitary neuroendocrine tumour'; (ii) recl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Owing to its invasiveness and progression, pituitary adenoma—especially NFPA—is difficult to resect and treat. Recently, the term “pituitary neuroendocrine tumor” was proposed for pituitary adenoma to emphasize its unpredictable nature [24]. However, the relationship between molecular alterations and clinical outcome in pituitary disorders is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its invasiveness and progression, pituitary adenoma—especially NFPA—is difficult to resect and treat. Recently, the term “pituitary neuroendocrine tumor” was proposed for pituitary adenoma to emphasize its unpredictable nature [24]. However, the relationship between molecular alterations and clinical outcome in pituitary disorders is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MEN1 mutation in PitNETs is not specific to the cell type. Early studies suggested that TP53 inactivation and RAS mutations were features of carcinomas [ 68 , 69 ]. However, the genetic factors underlying the majority of sporadic PitNETS remain unknown and epigenetic alterations are thought to be common.…”
Section: Implications For Site-specific Classificationmentioning
confidence: 99%
“…This is a cross-sectional single-center observational study conducted in children and adolescents with brain tumors at the Pediatric Clinic, Clinical Service of Endocrinology, Diabetes and Metabolism, and the Neurosurgery/Neuro-oncology unit, IRCCS Istituto Giannina Gaslini, University of Genova. Sixtythree patients (34 males and 29 females) with a median age of 13 years (IQR: [10][11][12][13][14][15][16][17][18][19] were evaluated at a median time of 5.5 years (IQR: 2.2-8.3) after the diagnosis of brain cancer when samples for the measurements of auto-antibodies were taken.…”
Section: Subjectsmentioning
confidence: 99%
“…Despite the fact that the neoplastic component of CNS germinoma is the germ cell, these tumors also exhibit an abundance of quiescent tumor-infiltrating lymphocytes (10). Hence, inflammatory lesions of the pituitary/pituitary stalk/hypothalamus including the chronic lymphoplasmacytic process known as lymphocytic infundibulo-hypophysitis, autoimmune hypophysitis, granulomatous inflammation, and xanthomatous hypophysitis (1,11,12) may raise diagnostic difficulties with tumors like germinomas. Both lymphocytic hypophysitis with central diabetes insipidus (CDI) and subsequent hypopituitarism masking a suprasellar germinoma, and isolated lymphocyte infiltration of pituitary stalk preceding the diagnosis of germinoma were reported (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%